2019
DOI: 10.5115/acb.19.128
|View full text |Cite
|
Sign up to set email alerts
|

A temporary disc-like structure at the median atlanto-axial joint in human fetuses

Abstract: During observations of mid-term and late-stage fetuses, we found a joint disk-like structure at the anterior component of the median atlanto-axial joint. At mid-term, the disk-like structure was thick (0.1-0.15 mm) relative to the sizes of bones surrounding the joint. However, it did not completely separate the joint cavity, and was absent in the inferior and/or central part of the cavity. This morphology was similar to the so-called fibroadipose meniscoid of the lumbar zygapophysial joint that is usually seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A major proportion of the present specimens had been used for our recent study of a temporarily appearing disk in the median atlanto-axial joint (Sakanaka et al, 2019). The present specimens had been stored in formalin solution for more than 10 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major proportion of the present specimens had been used for our recent study of a temporarily appearing disk in the median atlanto-axial joint (Sakanaka et al, 2019). The present specimens had been stored in formalin solution for more than 10 years.…”
Section: Methodsmentioning
confidence: 99%
“…We have also used fetal specimens for investigation of the neurodural junction in the thoracic spinal cord (Cho et al, 2016). Moreover, we have become familiar with the topographical anatomy of the atlanto-occipital region through our recent study of a temporary disk-like structure appearing at the median atlanto-axial joint (Sakanaka et al, 2019). Consequently, using human fetuses near term, the aim of this study was to demonstrate the morphology and individual variations in the suboccipital fascial configuration including the myodural bridge candidate.…”
Section: Introductionmentioning
confidence: 99%
“…The sectional planes were sagittal (24 fetuses) or horizontal (six fetuses from the midterm and near‐term groups). Some of the cervical sagittal sections were used in our previous studies (Kitamura et al, 2019; Sakanaka et al, 2019). Most photographs were taken with a Nikon Eclipse 80.…”
Section: Methodsmentioning
confidence: 99%
“…Although it was out of the focus, our recent study of the fetal occipitovertebral junction (Ishii et al, 2020; Kitamura et al, 2019; Sakanaka et al, 2019) demonstrated that the morphology of the subaxial cervical ZJ was quite different from that in adults. The cervical joint cavity (JC) is very large because it extends posteromedially along the vertebral lamina far beyond the articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 19 embryos and fetuses at gestational week 6 to 7 (crown-rump length of 15–27 mm) were obtained following miscarriages and ectopic pregnancies managed at the Department of Obstetrics, Complutense University of Madrid (Madrid, Spain). Serial horizontal and sagittal sections of the fetal heads were stained with hematoxylin and eosin, Masson trichrome, or Azan trichrome according to our recent research methods [ 7 - 9 ]. After examination, the stained sections were donated to the collection maintained by the Institute of Embryology, Complutense University of Madrid.…”
Section: Methodsmentioning
confidence: 99%